PENERAPAN FINGER PAINTING THERAPY PADA AN.H USIA PRASEKOLAH (3 TAHUN) DALAM MENINGKATKAN KETERAMPILAN MOTORIK HALUS DENGAN PENYIMPANGAN PERKEMBANGAN DI PUSKESMAS CIMAHI SELATAN - Siti Zulva; Shanti Khoirum Prathiwi; Fany Haifa Latifah (Yayasan Putra Sukamanah Sejahtera, 2025)
The development of preschool-aged children starts from the age of 3-6 years; not all children can pass through the developmental stages well, which is why the development of preschool-aged children is an important aspect to pay attention to. 15-20% of preschool-aged children suffer from fine motor development disorders. This study aims to determine how the application of finger painting therapy activities affects 3-year-old children with fine motor development deviations at the Cimahi Selatan Health Center. The case study method used in this research employs a descriptive design. Data collection was carried out through observation and interviews, as well as the Pre-Screening Development Questionnaire (KPSP) and fine motor assessment instruments. Deviations in fine motor development in preschool-aged children can hinder their ability to perform daily activities, such as writing and drawing. Finger painting therapy is a form of play therapy that can stimulate the development of children's fine motor skills. The results for An.H, with deviations in fine motor skill development before being given finger painting therapy according to the KPSP results, were doubtful (M) with a score of 1. After being given finger painting therapy, the results were appropriate (S) with a score of 3, indicating an improvement in An.H's fine motor skills. The results of this case study show a significant improvement in An.H's fine motor skills after continuous finger painting therapy, with a final score of 83.3% (very good). This study shows that finger painting therapy for preschool- aged children can enhance the development of fine motor skills and is effective in improving hand- eye coordination, as well as increasing the child's functional abilities in daily activities.